Cytoplasmic Vacuolation and Tapetal Changes Induced by a Novel Analgesic Agent in Beagle Dogs. (June 2019) - Takahashi, Kei; Morita, Yasuhiro; Udagawa, Shuji; Yamakawa, Seiki; Watanabe, Dai; Mutsuga, Mayu; Nakajima, Mayumi; Kohno, Makoto; Miyamoto, Yohei; Oshida, Keiyu
Drug-induced unique cytoplasmic vacuolation was found in the subchronic oral toxicity study of 4-dimethylamino-1-{3-(1-methyl-1H-imidazole-2-yl)propanoyl}piperidine (DMIP), a potential therapeutic agent for neuropathic pain, in beagle dogs. In the first study, DMIP was administered at a dose of 250, 500, or 1, 000 mg/kg/day once daily for 14 days. Discoloration of tapetum lucidum accompanied by tapetal swelling was observed at ≥250 mg/kg/day. The tapetal swelling was correlated to the light microscopic observation of cytoplasmic vacuolation in tapetal cells, and similar vacuolation was observed in several other tissues, including the coronary artery and aortal arch, in a dose-dependent manner. Immunohistochemistry for lysosomal-associated membrane protein 2 indicated that the vacuoles were enlarged lysosomes. However, the nature of these vacuoles was different from that of phospholipidosis because no lamellar bodies were observed. In the second study, DMIP was administered at a dose of 10, 50, or 250 mg/kg/day once daily for 14 days followed by a 14-day recovery period. Tapetal changes and systemic vacuolation were not observed at ≤50 mg/kg/day, and vacuolation observed at 250 mg/kg/day was reversible. A few reports have described the enlargement of lysosomes not attributable to phospholipid accumulation. Our findings provide further information about the toxicological implications of drug-induced lysosomal swelling.